Ukama Ustawi Pause and Reflect report - Hanke-Louw, Nora; Shrestha, Manisha; Jacobs-Mata, Inga; Girvetz, E. (International Water Management Institute (IWMI), 2023)
The CGIAR Initiative on Diversification in East and Southern Africa (also known as Ukama Ustawi) Pause and Reflect Week was planned in line with the CGIAR Pause and Reflect guidelines, and the needs of the initiative. To achieve the objectives of reconnecting as a Ukama Ustawi Community of Spirit (CoS), critical reflection on Ukama Ustawi in 2022 and replan for 2023, the core team met for five days and invited the Ukama Ustawi CoS to join for five days in Magaliesburg, South Africa. Throughout the report, the speakers and participants are referred to by their first names. Generally, the atmosphere in Ukama Ustawi is cordial, fun, and respectful and allows for open, uninhibited, and critical discussions.